2019
DOI: 10.5045/br.2019.54.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism in Chinese pregnant women: Hong Kong venous thromboembolism study

Abstract: BackgroundPrevious Caucasian studies have described venous thromboembolism in pregnancy; however, little is known about its incidence during pregnancy and early postpartum period in the Chinese population. We investigated the risk of venous thromboembolism in a “real-world” cohort of pregnant Chinese women with no prior history of venous thromboembolism.MethodsIn this observational study, 15,325 pregnancies were identified in 14,162 Chinese women at Queen Mary Hospital, Hong Kong between January 2004 and Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…In epidemiological studies, the incidence of VTE was three-to four-fold lower in Chinese compared to Caucasian individuals, while the VTE risk in African Americans appears to be higher than that in Caucasians. [16][17][18] In an Irish cohort of 83 COVID-19 patients, mainly of Caucasian ethnicity, baseline D-dimer levels were significantly increased in patients with a fatal outcome and/or Hyperkoagulabilität, hervorgerufen durch Entzündung und virale Endotheliitis, entwickeln einige Patienten mit fortgeschrittener Erkrankung eine Koagulopathie, die die Laborkriterien einer disseminierten intravasalen Gerinnung erfüllt, jedoch selten mit einer Blutungsneigung einhergeht. Wie andere Fachgesellschaften hat auch die GTH e.V.…”
Section: Evidence From Europe and North Americaunclassified
See 1 more Smart Citation
“…In epidemiological studies, the incidence of VTE was three-to four-fold lower in Chinese compared to Caucasian individuals, while the VTE risk in African Americans appears to be higher than that in Caucasians. [16][17][18] In an Irish cohort of 83 COVID-19 patients, mainly of Caucasian ethnicity, baseline D-dimer levels were significantly increased in patients with a fatal outcome and/or Hyperkoagulabilität, hervorgerufen durch Entzündung und virale Endotheliitis, entwickeln einige Patienten mit fortgeschrittener Erkrankung eine Koagulopathie, die die Laborkriterien einer disseminierten intravasalen Gerinnung erfüllt, jedoch selten mit einer Blutungsneigung einhergeht. Wie andere Fachgesellschaften hat auch die GTH e.V.…”
Section: Evidence From Europe and North Americaunclassified
“…In epidemiological studies, the incidence of VTE was three- to four-fold lower in Chinese compared to Caucasian individuals, while the VTE risk in African Americans appears to be higher than that in Caucasians. 16 17 18 …”
Section: Evidence From Europe and North Americamentioning
confidence: 99%
“…A hypothesis suggesting the role of coagulation having a major effect in the pathogenesis of COVID-19 was further examined to see differences among different races and ethnicities ( Fogarty et al., 2020 ; Zhou F. et al., 2020 ). Since thrombotic risk differs between races and ethnicities, studies show that African Americans are at higher risk than Caucasians populations ( Huang et al., 2019 ) and the Chinese population has a lower risk of venous thrombo-embolism which is around 3-4 times lower than that in Caucasians ( Liao et al., 2014 ). A study performed in Ireland examining the coagulation in Caucasian patients, the data observed showed a significant relationship between coagulopathy and severity of COVID-19 disease ( Fogarty et al., 2020 ).…”
Section: Genetic/molecular Predisposition and Underlying Conditions Amentioning
confidence: 99%
“…22 The risk of deep vein thrombosis in Chinese patients is generally one-quarter to one-third of that of white patients, whereas the risk in African-Americans is markedly higher than in white people. 23,24 Therefore, ethnicity needs to be considered when determining anticoagulative strategies for COVID-19 patients. As pulmonary artery thrombosis is frequently observed even in patients undergoing anticoagulation therapy, anticoagulants need to be administered in sufficient amounts.…”
Section: Treatment Of Covid-19-associated Hypercoagulabilitymentioning
confidence: 99%